(untitled) (Pubmet, 2022)
The ‘Ivory Tower’ is a metaphor often used to describe an elitist and self-sufficient research culture, which is relatively indifferent to whether research is useful for the society or whether the society is aware of such research and its results. Outside the tower, in contrast, citizen science is carried out, presentations are given at community centres, interviews are given to journalists, exhibitions held, popular science articles written, all to make research understandable and digestible outside the tower. Over the past 50 years, scientists have alternately been chased up and down from the socalled Ivory Tower. On the one hand, the current New Public Management paradigm demands measurable results from the universities, such that can easily be reported to the funders. The easiest way to meet this demand is to rely on a single-track publication strategy focused on publishing research results in international peer-reviewed journals. On the other hand, university laws, journalists, the general population, politicians, and a large group of socially committed researchers regularly argue that other activities held below the tower should also count and adorn researcher’s CV. The good news is that on 8 July 2022, an agreement has been finalised to reform current methods for assessing researchers and research quality. The initiative comes from the EU Commission, and the process has been short and effective. If the agreement is adopted, it could bring about a different, flexible, and multi-pronged publishing system that encourages researchers to publish on many alternative platforms and as such that they may inhabit and populate the area below the ivory tower and all its floors.